AVICENNIA OBSERVATION FIELD GUIDE IN MANGROVE AREA, SUNGAI RASAU, INDONESIA - Ahadina Husnul Mawadah; Mahrudin Mahrudin; M. Arsyad (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Local potential can be utilized in biology learning, especially to increase students' knowledge. This kind of learning is called contextual. The subject "Plant Ecology" is a compulsory subject, containing the concept of population in teaching. Based on the information, it is known that the population concept material still does not come from local potential. The purpose of this study was to analyze the Avicennia (Ind; Api-api) observation guide in the Mangrove Area, Sungai Rasau, Indonesia, as an enrichment material for the "Plant Ecology" course. This development research uses secondary data. The research data is included in the teaching materials as a field guide, and refers to Tessmer's formative evaluation. The field guide was validated by three experts, and got a total score of 92.02% (valid), and deserves to be applied without revision. However, revisions are still made in accordance with a few suggestions from the validator.